Thermal properties of Acacia mangium cross laminated timber and its gluelines bonded with two structural adhesives - Mohd Yusof, Norwahyuni; Md Tahir, Paridah; Seng Hua, Lee; Athiyah Sabaruddin, Fatimah; Suffian James, Redzuan Mohammad; Asim Khan, Mohd; Ching Hao, Lee; Muhammad Roseley, Adlin Sabrina (Maderas. Ciencia y Tecnología, 2020)
The properties of CLT can be affected by the type of adhesives used. The thermal properties of the adhesive that joins the timber together is essential to determine the thermal endurance of the CLT product. In this study, two types of adhesives were used to join the cross laminated timber (CLT) manufactured from Acacia mangium namely phenol resorcinol formaldehyde (PRF) and one component polyurethane (PUR). The thermal properties of the adhesives, A. mangium wood and the gluelines were determined via Thermogravimetric Analysis (TGA) and Dynamic Mechanical Analysis (DMA) tests. The TGA test showed that PRF adhesive had higher degradation temperature at 530 ˚C compared to PUR adhesive at 430 ˚C. Meanwhile, the PRF adhesive as a glueline in CLT also showed better thermal resistance where a higher amount of residue of 20,94 % was recorded at temperature up to 900 ˚C compared to PUR glueline with 18,26 % residue. The integrity of the CLT over temperature were determined via DMA test and the results showed that PRF adhesive as glueline had superior properties, indicating better interfacial bonding with the woods.